Santri Smoking Behavior Determinant At "X” Islamic Boarding School in Jember Regency - Rokhmah, Dewi; Muhammad Adilya Rahman; Erwin Nur Rif'ah (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Smoke is a risk factor for various infections and increased severity of respiratory tractisease. Deaths due to smoking in the world in 019 reached 8 million people per year, while death as a consequence of cigarettes in Indonesia reached 230,000. Objective: The aim of this study was to know the determinant behavior of teenage student smokers at boarding school X and including predisposing factors, enabling factors, and reinforcing factors. Methods: This study was conducted with a quantitative method with a cross-sectional approach. Population is santris in cottage boarding school X on SMP and SMA levels as many as 325 students with a total sample of 198 students who are determined with probability sampling. Results: Study shows as many as 59.6% respondents smoked (respondents aged 12-15 years (65.7%) with a stay of 1-3 years (86.9%). Knowledge good (53%), negative attitude (94.9%) and negative values (79.3%) means no health support (70.2%), facilities infrastructure supporter no support (54%), kiai no support (96.5%), boarding school administrator no support (88.4%) and friend no support (80.8%). Bivariate analysis Results show variables that have a connection - age (p-value=0.004), education level (p-value=0.000), attitudes (p-value=In the majority of santri smoking, were 12-16 years old with a duration of 1-3 years and for level highest education is junior high school / equivalent. Smoke behavior was influenced by variables of age, level of education, attitudes, values, and health facility. Application rule ban smoke among santris needs to be upgraded with signs warning of a smoking ban in certain places that are often frequented by santri   the form of posters or board warning as well as accompaniment from public health centers.